HUBUNGAN KONSEP DIRI DENGAN KOMUNIKASI INTERPERSONAL GURU TK DI KECAMATAN TAMPAN KOTA PEKANBARU - Sri Damaiyanti; Zulkifli Zulkifli; Nurlita Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Absract: This research aims to determine the relationship between self-concept and interpersonal communication kindergarten teacher in Tampan District Pekanbaru City. The population in this research was 274 teachers. The research sample was 163 teachers. The data collection techniques, namely in the form The data analysis using scale trials and analysis of statistical methods with SPSS for Window Ver. 16. of Likert scale. The hypothesis of this research is that there a positive and significant relationship between self-concept and interpersonal communication kindergarten teacher in Tampan District Pekanbaru City. It can be seen from the analysis of data obtained tcount ttable 8.266 while the value (5%) (df = n-2 = 163-2 = 161) ttable value 1.960. Because of t greater than t table or 8.266> 1, 960, it means that there is a positive and significant relationship between self-concept and interpersonal communication kindergarten teacher in the Tampan District Pekanbaru City. The resulting coefficient determinant is equal to r2 = 0.296 and p = 0.000 (p <0.05), it can be seen that the self-concept giving effect of 29, 6% of the interpersonal communication kindergarten teacher Tampan District Pekanbaru City.Key words: Self-Concept, Interpersonal Communication